2004
DOI: 10.1128/aac.48.3.897-902.2004
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Detection-Based Functional Assay for High-Throughput Screening for MraY

Abstract: We have developed a novel assay specific to MraY, which catalyzes the first membrane step in the biosynthesis of bacterial cell wall peptidoglycan. This was accomplished by using UDP-MurNAc-N -dansylpentapeptide, a fluorescent derivative of the MraY nucleotide substrate, and a partially purified preparation of MraY solubilized from membranes of an Escherichia coli overproducing strain. Two versions of the assay were developed, one consisting of the high-pressure liquid chromatography separation of the substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 29 publications
(31 reference statements)
4
69
1
Order By: Relevance
“…The difficult production of MraY and other MPs involved in peptidoglycan biosynthesis so far have largely retarded the detailed study of their biosynthetic mechanisms and the search of novel antibacterials. Nevertheless, the substrate specificity of MraY was intensively studied and a number of enzymatic assays designed for throughput screening of inhibitors have been developed (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…The difficult production of MraY and other MPs involved in peptidoglycan biosynthesis so far have largely retarded the detailed study of their biosynthetic mechanisms and the search of novel antibacterials. Nevertheless, the substrate specificity of MraY was intensively studied and a number of enzymatic assays designed for throughput screening of inhibitors have been developed (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Solapure et al 8 reported an IC 50 of 360 nM in an assay containing 9 µM UNAM-pp, 0.1% Triton X-100, 25 mM Mg 2+ , and only endogenous C 55 P from the membranes used as a source of MraY. Stachyra et al 7 reported an IC 50 of 2 µM in an assay containing 50 µM C 55 P and 25 µM dansyl-UNAM-pp in 0.1% TX-100 and 50 mM Mg . Several factors may contribute to the observed differences, including differences in the substrate, detergent, Mg…”
Section: Resultsmentioning
confidence: 99%
“…The column was eluted with 100%A for 3 min, a gradient of 100%A to 100%B in 2 min, then 100%B for 5 min. 7 The flow rate was 0.5 mL/min at room temperature. The B-UNAM-pp peak eluted at 5.7 min.…”
Section: Preparation Of N-bodipy-fl-unam-pp (B-unam-pp)mentioning
confidence: 99%
“…10 IC 50 values reported using other assays in the range of 360 nM to 2 mM. 8,11,12 Z 0 values for the 1,536-well assay during the HTS were equal to or greater than 0.6 and the signal-to-background ratio was 1.4-1.6. Primary MraY HTS and associated confirmatory assays were screened using the three compound libraries described in the ''Materials and Methods'' section.…”
Section: High-throughput Screeningmentioning
confidence: 89%